Effication Test of Srikaya Seeds Extract (Annona squamosa L.) to Kill Aedes aegypti Larvae in Laboratory - Eny Sofiyatun; Joko Malis Sunarno (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Dengue fever is still becoming national health problem. Control of it have been done but the cases still increase significantly. One way to control the disease is vector control of Aedes sp. Generally, people prefer to choose synthetics insecticides than botanical insecticides and environmental management. Used of synthetics insecticides causing mosquito resistence.Objectives: To know the potency of Srikaya seeds as botanical larviciding to Aedes aegypti larvae as main vector of dengue fever.Methods: Experimental study with cross sectional design have done with three times repeat of efication test. Extraction process of Srikaya seeds according to Kardinan (2000). Concentration of Srikaya seeds extracts are 25%, 50% and 75% with control. Population of the study is Ae.aegypti larvae (L3) from Entomology Laboratory of Balai P2B2 Banjarnegara. Data was observed are mortality and growth of larvae into pupa and imago stages. Probit analyzed was done and describes by graphic and table.Results: Srikaya seeds extracts effect to Ae. aegypti larvae and causing larvae death for each concentration test (concentration 25%, 50%, and 75%). Growth of Ae.aegypti larvae also decreases that  shown by pupa failure to reach imago stages after 6th day. This result shows that Srikaya seeds extracts have potency as larvicide might be due to annonain and squamosin content as acetogenine that can cause mortality of some insects Ordo.Conclusion: Srikaya seeds extracts have potency as larvicide on Aedes aegypti larvae. Srikaya seeds extract have a potency as botanical insecticides, not only to pest control on farm and poultry but also in vector diseases control.Keywords: Srikaya seeds extracts, larvicide, Aedes aegypti, mortality